On receiving the witness: A keynote as a site of care - martin, timothy (YU-WRITE: Journal of Graduate Student Research in Education, 2023)
At this year’s conference, I was privileged to participate as one of the keynote speakers. Drawing on my dissertation, I gave a lecture on the pedagogical work and archival practices of an event known as The Toronto Homeless Memorial. This brief reflection is inspired by the way in which my words were received by conference attendees—and, more broadly, the work of listening to those who bear witness to violence. I, along with many others, relate to the memorial on a personal level; my research is a practice of witnessing and of partnering with the testimony of the memorial organizers. Influenced by Ann Chinnery’s (2013) thinking, I conceptualize the work of storylistening as facilitating cross-temporal relationality with the past—specifically, with past-others rendered silent and invisible. By receiving the testimony of the witness, we make possible moments of interruption and encounter for/with those abjected from public regard.